Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Pada Materi Sistem Persamaan Linear Tiga Variabel - Mulyani, Sri; Haerudin, Haerudin (Media Pendidikan Matematika, 2021)
The purpose of this study was to describe students' mistakes in solving story problems on the material of the three-variable linear equation system (SPLTV) based on the Newman procedure to minimize the occurrence of the same errors in the future. The approach used is a qualitative approach with descriptive methods. The subjects in this study were 25 students of class X SMAN 14 Bekasi. The test instruments used was 2 items in the description. In this study using errors according to Newman to analyze student errors. From the results of the analysis, it was found that the average error rate of students in answering SPLTV story questions was 34.4% and the remaining 65.6% of students could answer correctly and correctly. Of the two questions given, question number 1 had more percentage of students who made mistakes. There are various kinds of mistakes made by students, based on the error analysis according to Newman, there was a reading error of 0% because none of the students read the questions wrongly, the error in understanding was 30.23% because the students did not write known and asked, the transformation error was equal to 20.93% because the students were not able to transform the questions given into a mathematical form so they could not make mathematical models, 24.42% error in processing skills was due to the lack of students' accuracy in calculating which resulted in errors, and errors in writing the final answer of 24, 42% because the students were incomplete in making conclusions.